Trajetória educacional de estudantes com deficiência visual da Universidade Federal do Espírito Santo - Silva, Ana Claudia Fontes da (2022)
With the proposal of constituting the educational trajectory of students with visual impairments, the research had as general objective to investigate the educational trajectory of students with visual impairments at Ufes/Alegre and their experiences in higher education. For this, it was sought to know the process of schooling of students at different levels in education; reflect on signs and marks of ableism and its materialization during the educational trajectory of students and identify the existing conditions related to the participation, permanence and success of students in higher education. Having research with a qualitative approach, the investigation method was Life History (HV), which was treated in this research as Topical Life History (HVT), for focusing on certain stages of two university students’ life’s enrolled at Ufes/Alegre. Data production took place through Narrative Interviews (NE), a form for identifying students and the research notebook. The assumptions that gave the theoretical basis were the historical-cultural perspective of human development by Vygotsky (1896-1934), especially the studies of defectology, and the current studies on ableism. In addition, an incursion was made on the regulations related to the education of people with impairments. The students' narratives and the events they experienced revealed that, in society and even in educational places, the focus of the research, there is a coexistence of the biomedical conception with the social conception of deficiency and that their trajectories are marked by elements that sometimes hinder and sometimes help to build strategies/possibilities so that students with impairments can be at different levels of education on equal terms with others, by rights. In addition, by sharing their experiences, joys and pains, challenges and victories, the students contributed to the discussion related to special education from the perspective of inclusive education, and based on this dialogue, the importance of accessibility centers structured with exclusive professionals in higher education is highlighted, as well as in multifunctional resource rooms in basic education. Just as important is the offer of continuing education for professionals and the need to break with homogenizing practices, because it is essential to consider human diversity and the singularities related to the education of people with impairments. Therefore, it is essential to understand the ableism as a paradigm based on limiting and negative beliefs, which needs to gain visibility, from the social conception of deficiency and be extinguished. Based on the students' narratives, it is necessary to understand that it is urgent to mobilize and expand this debate in academic productions and, definitely, in spaces where ableism occurs, in everyday life, but mainly in the educational places. Change requires reviewing practices, above all, on the part of teachers who, due to ableism attitudes and attitudinal barriers, make choices that disadvantage and harm students with impairments and their education.